Scaramouche - Sabatini, Rafael, 1875-1950; Wilson, Carey, 1889-1962; Millar, Ronald, 1919-1998; Froeschel, George; Sidney, George, 1916-2002; Granger, Stewart, 1913-1993; Parker, Eleanor, 1922-2013; Leigh, Janet; Ferrer, Mel (Archive collection., 2012)
Disguised as a stage clown, Andre Moreau perfects his skill as a swordsman in order to strike a blow for the French Revolution.